Ipilimumab: an investigational immunotherapy for glioblastoma. (1st November 2020) - Youssef, Gilbert; Dietrich, Jorg
ABSTRACT: Introduction: Glioblastoma (GBM) is the most common primary malignant central nervous system tumor and has a poor overall outcome despite an aggressive standard-of-care treatment. Hence, better therapeutic modalities are necessary. Immunotherapy is a novel modality that has an indirect action against the tumor cells through activation of an anti-tumor immune response. Areas Covered: Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) belongs to a class of molecules called immune checkpoints that are inherently expressed on immune cells and lead to attenuation of the immune response. Inhibition of such molecules has been approved for the treatment of melanoma, and prolonged survival and complete responses have been reported in preclinical GBM mouse models. Ipilimumab inhibits CTLA-4 and is being investigated for the treatment of GBM, alone or in combination with other treatment modalities, in various preclinical and clinical studies, the results of the most relevant of which are discussed in this review. Expert Opinion: Combining ipilimumab with other immunotherapy modalities and using it in specific conditions may increase the rate of objective responses in patients with GBM.